Agronomic and bromatological characteristics of genotypes of Carthamus tinctorius l. Potential for the cerrado region - Silva, Leonardo Máximo; Sanglard, Demerson Arruda; Nogueira, Ariane da Silva; Dourado, Luan Rocha; Silva, Leovandes Soares da; Lessa, Marcos Fernando Gonçalves (Brazilian Journal of Production Engineering, 2024)
Safflower (Carthamus tinctorius L.) can be an alternative crop in the off-season in Cerrado regions because it has high productivity with low demand for water during its cycle, in addition to being a fully mechanized crop. It is currently cultivated mainly for the production of edible oil, cooking oil and for pharmaceutical applications. In view of this, the present work aims to evaluate the agronomic performance and the bromatological and morphological characteristics of 19 safflower genotypes in the semiarid north of Minas Gerais. The work was carried out at the Institute of Agricultural Sciences of the Federal University of Minas Gerais (ICA/UFMG). The design used was completely randomized with 19 treatments (where each genotype was considered as a treatment) with 16 replications. Morphological characteristics, crude protein and ether extract contents were evaluated. The data obtained were submitted to analysis of variance and the averages were grouped by the Skott-knott test and multivariate analysis (P<0.05). The evaluated genotypes showed protein contents varying between 18.65% and 26.69%. The ether extract contents of the grains of the evaluated genotypes ranged from 18.54% (genotype 63) to 24.98% (genotype 119). Genotypes 73, 77 and 63 have superiority in their morphological and bromatological characteristics, thus allowing further research to be carried out in order to obtain genetic material with great potential for the Brazilian semi-arid region.